The effectiveness of complementary and alternative medicine therapy in reducing pain in diabetic neuropathy: A systematic review - Syahriyani, St; Yusuf, Saldy; Syam, Yuliana (YCAB Publisher & IAKMI SULTRA, 2021)
Background: Pain is quite often felt in approximately 30 to 50% of people with diabetic neuropathy. As a result, the quality of life is low, indicated by the high morbidity and mortality rates. The availability of symptomatic pharmacological agents has the potential to have side effects and adverse effects in the elderly and in addition to the high risk of addiction. Complementary therapy and alternative medicine in chronic pain are clinically safe, cost-effective, and affordable. However, scientific evidence of its effectiveness is limited.Objective: This systematic review aims to evaluate the intervention modalities and the effectiveness of complementary and alternative medicine therapy in diabetic neuropathy pain.Methods: The searched literature databases included PubMed, ProQuest, ScienceDirect, EBSCO host, DOAJ, Clinical Key for Nursing, and Cochrane. The criteria for the article, among others, focus on complementary therapy and alternative medicine in diabetic neuropathy pain, publications in the last five years, full text, and in English. Results: Fifteen articles were identified in reporting the effectiveness of complementary therapy and alternative medicine in reducing diabetic neuropathy pain, including mindfulness-based stress reduction, mindfulness meditation, relaxation, whole-body vibration, Abzan, aerobic resistance training, nano curcumin, Citrullus colocynthis, dietary, acupuncture, laser, and reflexology.Conclusion: Most scientific evidence reports the effectiveness of complementary and alternative medicine therapies in reducing pain in diabetic neuropathy, thus strengthening its application as an adjunct to conventional medicine is needed.